Penegakan Hukum Terhadap Peredaran Rokok Tanpa Cukai di Indonesia - Nyoman Dita Ary Putri; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2022)
Indonesia as a developing country, one of whose income is through Customs and Excise levies, the responsibility of which will be borne by the apparatus of the Directorate General of Customs and Excise, such as cigarettes. However, there are still many cigarette factories or entrepreneurs who commit violations in the form of distributing cigarettes without excise in Indonesia. The purposes of this study are to analyze the legal regulation of the circulation of excise-free cigarettes in Indonesia and law enforcement efforts against the distribution of excise-free cigarettes in Indonesia. This research method is a normative legal research method with a conceptual approach. The technique of collecting legal materials used in this research is by recording in the documentation. Sources of legal materials used in the form of primary, secondary, and tertiary legal sources. After the data was collected, then analyzed systematically, the results of the study revealed that the circulation of cigarettes without excise in Indonesia is regulated in Article 4 which states that cigarettes are excisable goods because they are processed tobacco products and Article 29 of Law Number 39 of 2007 which states that goods are subject to excise. must be attached with excise stamps or affixed with other signs of payment of excise duty to be offered, delivered, sold, or made available for sale. Law enforcement efforts against excise-free cigarettes in Indonesia include preventive (prevention) and repressive (enforcement) law enforcement efforts. Law enforcement against the distribution of cigarettes without excise may be subject to criminal penalties in the form of imprisonment and fines which are cumulative (combined) criminal penalties.